Acid Corrosion Inhibition of Steel by Lamotrigine. (31st October 2012) - Shylesha, B. S.; Venkatesha, T. V.; Praveen, B. M.; Nataraja, S. E.
Abstract : Corrosion inhibition effect of lamotrigine on steel in 1.0 M HCl and 0.5 M H2 SO4 was studied by techniques like weight loss, polarisation, and electrochemical impedance spectroscopy. Results indicated that lamotrigine is more competent in HCl than in H2 SO4 and is justified by scanning electron micrographs. Protection efficiency increased with the concentration of inhibitor and decreased with temperature. Adsorption study revealed the comprehensive adsorption of lamotrigine molecules on steel surface.